The relationship between thrombocytopenia and intraventricular hemorrhage in neonates with gestational age - Idha Yulandari; Lily Rundjan; Muzal Kadim; Pustika Amalia; Haryanti F. Wulandari; Setyo Handryastuti (Paediatrica Indonesiana, 2016)
Background The prevalence of thrombocytopenia in neonates ranges from 22 to 35%, and one of the most feared complications is intraventricular hemorrhage (IVH). Previous research in Cipto Mangunkusumo Hospital (CMH), Jakarta reported a high incidence of IVH (43.47%) in infants with a gestational age of <35 weeks. Intraventricular hemorrhage causes disturbances in neurological development and can be fatal. In Indonesia, research on the relationship between thrombocytopenia and IVH has been limited.Objective To study the relationship between thrombocytopenia and IVH in neonates with gestational age <35 weeks and assess for a correlation between the severity of thrombocytopenia and the severity of IVH.Methods This cross-sectional study was performed by reviewing medical records in the Neonatology Division of the Child Health Department, University of Indonesia, CMH. Subjects were neonates hospitalized from January 2012 to December 2014 with IVH. Subjects were categorized into either mild to moderate IVH (grade ≤2) or severe IVH (grade >2). Thrombocyte counts were recorded on the same day as the diagnosis of IVH.Results The risk of severe IVH was 28.2% in neonates with thrombocyte counts <100,000/uL, and 10.4% in neonates without thrombocytopenia (P=0.014). Multivariate analysis revealed that gestational age <32 weeks and the use of respiratory support (ventilator and high frequency oscillatory ventilation) had significant associations with severe IVH. However, multivariate analysis did not show a significant relationship between thrombocytopenia and severe IVH (correlation coefficient = 0.21).Conclusion Thrombocytopenia is not significantly associated with the incidence of severe IVH based on multivariate analysis. Also, the severity of thrombocytopenia has no correlation with the severity of IVH.